Forest understory ant (Hymenoptera: Formicidae) assemblage in a Meridional Amazonian landscape, Brazil (2018)
Ants inhabit and exploit the most varied habitats from the underground to the forest canopy. However, studies on the diversity of arboreal ants are less frequent in the Amazon. In this paper we list arboreal ant species sampled in understory along four transects in a forest remnant in a South Amazonian landscape. The list includes 32 species, of which three (9 %) are new records for the state of Mato Grosso, Brazil, one of these species being sampled for the first time in Brazil.